Penggunaaan alat peraga petak-petak urutan bilangan pecahan bagi peningkatan kompetensi siswa dalam menentukan urutan tertentu dari sekelompok bilangan pecahan acak - Endang Sumarwanti (Action Research Journal, 2021)
The purpose of this study is to describe the impact of using props in number sequence plots. This research was conducted on Mathematics subject about sorting numbers in grade VI SD Negeri 01 Batursari, Talun District, Pekalongan Regency in two cycles. The use of teaching aids in the form of plots of number sequences that are explained systematically in learning by teachers can actually improve students' abilities and skills in sorting groups of numbers arranged in a certain order (from sequential to largest). The increase in the number of students who achieved learning completeness was at least 11 students (64.70%) to 14 students (82.35%). The class average also increased from 73.52 to 86.47. The use of appropriate media and teaching aids in learning must be planned and carried out by the teacher so that the message conveyed can be received by students as a whole and realistically, especially in learning mathematics.